2010
DOI: 10.1002/dac.1118
|View full text |Cite
|
Sign up to set email alerts
|

New dynamic ID authentication scheme using smart cards

Abstract: SUMMARYRecently, Yoon et al. and Wang et al. independently proposed a dynamic ID authentication scheme and claimed that their schemes can withstand the risk of ID-theft, and several attacks. In this paper, we first demonstrate that both of the proposed schemes cannot achieve the security requirement for user anonymity and resist an impersonation attack yet. Then, we shall propose a new dynamic ID authentication scheme to overcome the above security weaknesses. We formally analyzed our proposed scheme with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…This section analyzes our protocol using BAN-logic [22]. According to BAN-logic, symbols P and Q stand for principals, while X and Y represent statements.…”
Section: Security Proof Based On Ban-logicmentioning
confidence: 99%
“…This section analyzes our protocol using BAN-logic [22]. According to BAN-logic, symbols P and Q stand for principals, while X and Y represent statements.…”
Section: Security Proof Based On Ban-logicmentioning
confidence: 99%
“…BAN logic has been widely used in different works such as [18][19][20] to reason about their security validation.…”
Section: Formal Proof Based On Ban Logicmentioning
confidence: 99%
“…Recently, Tsai et al [20] proposed a dynamic ID authentication scheme using smart cards. They claimed that their scheme provides security against several potential attacks.…”
Section: Contribution Of This Papermentioning
confidence: 99%
“…Nevertheless, the scheme is exposed to password guessing attack, server masquerade attack and lack of password backward security [19]. Recently, a dynamic ID authentication scheme has been proposed [20] and claimed that this scheme provides security against several potential attacks and satisfies the essential needs of end users. However, it is shown that this scheme is vulnerable to impersonation attack, offline password guessing attack, fails to provide perfect forward secrecy and does not solve time synchronization problem [21].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation